The Schellingian Roots of Peirce’s idealism (Nóema, 2016)
This essay was written with two targets. The first one is to expose the main conceptual frame of Schelling’s Objective Idealism, highlighting theoretical aspects that may make explicit his realism and ontological indeterminism. The second target is to fulfill the possible interest of Peirce’s scholars taking into account that he declares his debt to Schelling’s philosophy as a very important source of inspiration for his scientific metaphysics, mainly his Objective Idealism, not accidentally a doctrine that shares the same name with Schelling’s one. Centered in the exposition of Schelling’s thought, this essay adopt the strategy of showing to Peircean scholars the similarities between both thinkers, without, nevertheless, a point to point comparison with Peirce’s doctrines. Then, the present text is destined to those who knows Peirce’s metaphysics guidelines and, being so, they would be apt to make the theoretical connections between both thinkers by themselves.
Keywords: Schelling; Peirce; idealism; Objective Idealism; Realism; Indeterminism